Performance of Concerto in B Minor By Oscar Rieding for Solo Marimba - Feroz, Alifianez Mahardika; Herdianto, Ferry; Marh, Fahmi; Syahputra, Ade (Musica: Journal of Music, 2024)
The marimba solo performance featuring the composition Concerto in B Minor is a work by O. Rieding adapted for the marimba. Originally composed for the violin, this piece was released in November 1909 in Leipzig by the publishing company Bosworth & Co. The work consists of three movements: Allegro moderato, Andante, and Allegro moderato. The objective of this performance is to demonstrate the adaptation of this piece for the marimba, focusing on the application of arpeggio techniques and various expression marks such as piano, forte, crescendo, decrescendo, mezzo forte, ritardando, and a tempo. The performance results illustrate the successful application of these techniques and expression marks, showcasing the performer's ability to interpret and convey the musical nuances of the composition. The performance methodology includes the conceptualization, preparation, and execution of the performance..